1984
DOI: 10.1111/j.1464-5491.1984.tb01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria Predicts Mortality in Noninsulin‐dependent Diabetes

Abstract: Forty-four non-insulin-dependent diabetics (NIDD), all with urine negative to Albustix, were studied in 1966/67. By the end of 1980, 17 had died, all but two from cardiovascular causes. All causes of mortality and time to death were significantly related in univariate analyses to age and to the overnight urinary albumin excretion rate (AER), but not to systolic and diastolic blood pressure levels or to duration of diabetes when the latter was corrected for age. Age and duration were highly correlated with each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
189
5
4

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(205 citation statements)
references
References 4 publications
7
189
5
4
Order By: Relevance
“…Microalbuminuria has also been considered an independent risk factor for cardiovascular disease [9][10][11]27]. Type 2 diabetic patients with microalbuminuria have elevated levels ofvon Willebrand factor (vWF) as a sign of endothelial dysfunction [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalbuminuria has also been considered an independent risk factor for cardiovascular disease [9][10][11]27]. Type 2 diabetic patients with microalbuminuria have elevated levels ofvon Willebrand factor (vWF) as a sign of endothelial dysfunction [24].…”
Section: Discussionmentioning
confidence: 99%
“…overnight urinary albumin excretion rate (AER) above 20 btg/min predicts overt diabetic nephropathy in both patients with Type 1 (insulin-dependent) [6,7] and Type 2 diabetes [8]. In addition, microalbuminuria is associated with increased cardiovascular mortality in patients with Type 2 diabetes [9,10]. Only a small proportion of this excess cardiovascular mortality in Type 2 diabetes can be explained by end-stage renal failure.…”
mentioning
confidence: 99%
“…Transverse cohort and longitudinal studies have demonstrated that microalbuminuria is a predictor of large vessel disease [3][4][5] . Its prevalence varies in patients with diabetes from 7.6 to 42% [18][19][20] .…”
Section: Arq Bras Cardiol Volume 73 (Nº 1) 1999mentioning
confidence: 99%
“…However, it is important to emphasize that glycemic control can influence specific phases of the metabolism of lipids, such as the reverse transport of cholesterol. Recently, it was demonstrated that the glycation of HDL, especially the subfraction HDL 3 , favors a faster and more efficient transfer of cholesterol from this fraction to apoprotein B-containing lipoproteins 41 . We did not observe an association between lipid disorders and CAD, as described in studies with diabetic and nondiabetic patients 39,42,43 .…”
Section: Arq Bras Cardiol Volume 73 (Nº 1) 1999mentioning
confidence: 99%
See 1 more Smart Citation